Global burden of Alzheimer’s disease and other dementias in adults aged 65 years and over, and health inequality related to SDI, 1990–2021: analysis of data from GBD 2021 - Wen Liu; Wei Deng; Xinhao Gong; Jinping Ou; Shuchun Yu; Shoulin Chen (BMC Public Health)
Abstract Introduction The disease burden of dementia in the elderly is predicted to rise, and dementia among older adults has become a crucial issue for public health. Quantifying the disease burden of dementia in the elderly can provide relevant areas and countries with scientific data to help them adjust their healthcare strategies. Methods We analyzed the disease burden of Alzheimer’s disease and other dementias among individuals aged 65 and older from 1990 to 2021; the relationship between mortality rates and disability-adjusted life years (DALYs) with socio-demographic index (SDI); conducted a frontier analysis of the disease burden across 204 countries; and quantified inequalities in age-standardized DALYs for Alzheimer’s disease and other dementias using the slope inequality index and concentration index. Results Globally, age-standardized DALYs and mortality rates for individuals aged 65 and older have declined over time. We find that the disease burden of dementia is significantly associated with SDI. High SDI countries have 169% higher baseline levels of dementia burden compared to low SDI countries, as estimated based on their current level of social development. Finally, our health inequality analyses reveal that while the overall trend of DALYs for dementia increases with SDI, the burden is primarily concentrated in populations with lower SDI, as non-developed countries account for the majority of the population. Conclusion The global population aged 65 and older experiences a significant reduction in healthy life expectancy due to dementia. The burden of disease in most countries is higher than the minimum disease burden associated with SDI in those countries. The burden of disease in low and middle SDI countries has been showing an increasing trend. The gap in disease burden among regions with different SDI levels is also continuously narrowing.